RECENT OBSERVATION OF FALSE GHARIAL (Tomistoma schlegelii) IN THE SEMBILANG NATONAL PARK (TNS) AREA, BANYUASIN REGENCY, SOUTH SUMATERA PROVINCE - Setiawan, Arum; Safri, Adios; Prima, Bayu; Kadarisman, Reza; Indrianti, Winda; Oktaberi, Redi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2019)
A research about False Gharial (Tomistoma schlegelii) which is a protected animal based on National Government Regulation Number 7 of 1999 and renewal of Permen LHK No. P92/MENLHK/SETJEN/KUM.1/8/2018 has been conducted on 15 until 19 September 2017 located in the region of SPTN 3 Hulu Benu River Muara Merang Village 3 Pancuran Village, and on 27 February until 04 March 2018 located in the region of SPTN 3 area Hulu Benu River Tanah Pilih Village, Berbak Sembilang National Park (TNBS), South Sumatra. This reaserch aims to monitoring the conditions of habitat and its populations for the purpose of conservation and management of TNBS areas to be more optimal. The methods used is direct monitoring during the day and night, indirect monitoring through information and interviews with citizens, as well as secondary data collection. The results obtained, were that there was an encounter and information about the existence of False Gharials measuring Â± 1 to 5 meters in the upper reaches of the Benu River in the Merang River, Rasau River, Bagan 2, Bagan 6 through Bagan 9. This resulted in the determination of the Benu River TNBS as an important habitat False Gharials that needs to be managed appropriately as conservation areas